2016
DOI: 10.1038/celldisc.2016.27
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin remodeler DDM1 promotes hybrid vigor by regulating salicylic acid metabolism

Abstract: In plants, hybrid vigor is influenced by genetic and epigenetic mechanisms; however, the molecular pathways are poorly understood. We investigated the potential contributions of epigenetic regulators to heterosis in Arabidposis and found that the chromatin remodeler DECREASED DNA METHYLATION 1 (DDM1) affects early seedling growth heterosis in Col/C24 hybrids. ddm1 mutants showed impaired heterosis and increased expression of non-additively expressed genes related to salicylic acid metabolism. Interestingly, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 57 publications
1
63
0
Order By: Relevance
“…The direction of the change in expression is opposite. We hypothesize that, depending on the parent combinations, the level of a particular gene product associated with heterosis may be different (Zhang et al, 2016a). In FT QTL interval 3_2, we identified a down-regulated candidate gene, encoding EMBRYO DEFECTIVE1703, in the same three epiHybrids.…”
Section: Identification Of Putative Loci Mediating Hybrid Performancementioning
confidence: 81%
See 2 more Smart Citations
“…The direction of the change in expression is opposite. We hypothesize that, depending on the parent combinations, the level of a particular gene product associated with heterosis may be different (Zhang et al, 2016a). In FT QTL interval 3_2, we identified a down-regulated candidate gene, encoding EMBRYO DEFECTIVE1703, in the same three epiHybrids.…”
Section: Identification Of Putative Loci Mediating Hybrid Performancementioning
confidence: 81%
“…Prior studies on Arabidopsis heterotic hybrids identified candidate genes underlying heterotic phenotypes in pathways of the circadian clock, flavonoid biosynthesis, auxin transport, or salicylic acid metabolism and response (Ni et al, 2009;Shen et al, 2012;Groszmann et al, 2015;Zhang et al, 2016a). A Gene Ontology analysis on differentially expressed genes in a met1-derived epiHybrid did not show an overrepresentation of particular gene categories; however, the study proposed a gene (RECOGNITION OF PERONOSPORA PARASITICA5) within an epigenetically regulated resistance gene cluster to be a possible candidate (Dapp et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that the developmental defects associated with protracted DDM1 deficiency may not only reflect misregulation of development-specific genes, but also the consequences of a metastable genome (Ronemus et al 1996; Zhang et al 2016). The RAM is extraordinarily sensitive to DNA damage, and undergoes PCD in response to genotoxic stress (Fulcher and Sablowski 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In Columbia-0 (Col)/C24 hybrids, an active copy of the chromatin remodeler DECREASE IN DNA METHYLATION (DDM1), which affects DNA methylation in all sequence contexts, is required for a wild-type level of heterosis, whereas the alterations in gene expression produced by transchromosomal methylation via the RNA-directed DNA methylation (RdDM) pathway do not appear to contribute to hybrid vigor (28,29).…”
Section: Discussionmentioning
confidence: 99%